Tamsulosin use in benign prostatic hyperplasia and risks of Parkinson's disease, Alzheimer's disease and mortality: An observational cohort study of elderly Medicare enrollees. - Kin Wah Fung; Fitsum Baye; Seo H Baik; Clement J McDonald (PLoS ONE, 2024)
Purpose To study the effects of benign prostatic hyperplasia treatments, namely: alpha-adrenergic receptor blockers, 5-alpha-reductase inhibitors and phosphodiesterase-5 inhibitors on the risk of Parkinson's disease, Alzheimer's disease and mortality. Materials and methods All male Medicare enrollees aged 65 or above who were diagnosed with benign prostatic hyperplasia and received one of the study drugs between 2007-2020 were followed-up for the three outcomes. We used Cox regression analysis to assess the relative risk of each of the outcomes for each study drug compared to the most prescribed drug, tamsulosin, while controlling for demographic, socioeconomic and comorbidity factors. Results and conclusions The study analyzed 1.1 million patients for a mean follow-up period of 3.1 years from being prescribed one of the study drugs. For all outcomes, patients on tamsulosin were used as the reference for comparison. For mortality, alfuzosin was associated with 27% risk reduction (HR 0.73, 95%CI 0.68-0.78), and doxazosin with 6% risk reduction (HR 0.94, 95%CI 0.91-0.97). For Parkinson's disease, terazosin was associated with 26% risk reduction (HR 0.74, 95%CI 0.66-0.83), and doxazosin with 21% risk reduction (HR 0.79, 95%CI 0.72-0.88). For Alzheimer's disease, terazosin was associated with 27% risk reduction (HR 0.73, 95%CI 0.65-0.82), and doxazosin with 16% risk reduction (HR 0.84, 95%CI 0.76-0.92). Tadalafil was associated with risk reduction (27-40%) in all 3 outcomes. More research is needed to elucidate the underlying mechanisms of these observations. Given the availability of safer alternatives for treating benign prostatic hyperplasia, caution should be exercised when using tamsulosin in elderly patients, especially those with an increased risk of developing neurodegenerative diseases.